Differences in Health-related Behaviors and Quality of Life among Older Adults with Multimorbidity Based on Latent Class Analysis - LIAO Yanming, ZHENG Xiao, XUE Yaqing, XIAO Shujuan, XUE Benli, LI Xinru, CHEN Yiming, ZHANG Mengjie, ZHANG Chichen (Zhongguo quanke yixue, 2024)
Background The severe trend of the aging population, the rapid increase in the prevalence of chronic diseases among older adults, and the greater prominence of multimorbidity have posed challenges to the prevention and treatment of chronic diseases in China. Adverse health-related behaviors are modifiable risk factors for chronic diseases. Exploring the latent classes of health-related behaviors in older adults with multimorbidity and their associations with quality of life will help identify the characteristics of their health-related behaviors and uncover risk behaviors affecting the quality of life, providing references for precise health management to improve the quality of life of older adults. Objective To explore the latent classes of health-related behaviors in older adults with multimorbidity and the differences in the quality of life among the different classes. Methods Based on the baseline data from the Community Health and Behavior of the Elderly Panel Study (CHBEPS) conducted by our team in 2021, a total of 1 395 older adults aged 60 years and above with multimorbidity were included as study participants. A self-designed questionnaire was used to collect basic information, including disease status, smoking status, alcohol consumption, and dietary preferences of the participants. The Pittsburgh Sleep Quality Index (PSQI), International Physical Activity Questionnaire-Short-Chinese Version (IPAQ-S-C), and Lubben Social Network Scale-6 (LSNS-6) were used to assess staying up late, physical activity, and social network of the participants, respectively. The EuroQol five-dimensional five-level questionnaire (EQ-5D-5L) was used to measure the quality of life of the participants. Latent class analysis of health-related behaviors among older adults with multimorbidity was conducted using Mplus 8.3 software. Based on the fitted model, the different latent classes of health-related behaviors among older adults with multimorbidity were used as groups, and the Kruskal-Wallis and Wilcoxon rank-sum tests were performed using SPSS 26.0 software to analyze the differences in quality of life among these groups. Results Four latent classes of health-related behaviors were identified among older adults with multimorbidity, which are named the health behavior group (n=280), risk behavior group (n=366), comprehensive behavior group (n=173), and adverse behavior group (n=576). There were statistically significant differences in quality of life among the four latent classes (P<0.05). Specifically, the quality of life in the health behavior group was higher than that in the risk behavior group and adverse behavior group (P<0.05) . Conclusion When implementing precise health management for older adults with multimorbidity, the characteristics of their health-related behaviors should be taken into account. Special attention should be given to those with a higher probability of behaviors such as smoking, alcohol consumption, and a preference for sweet, spicy, and salty tastes, as well as those with a lower probability of behaviors such as a balanced diet, regular consumption of vegetables and fruits, and social networks. Additionally, measures targeted at addressing common issues such as insufficient physical activity should be implemented to improve the effectiveness of health management and the quality of life of older adults with multimorbidity.